Fabrication and Characterization of Polysulfone-Zeolite ZSM-5 Mixed Matrix Membrane for Heavy Metal Ion Removal Application - Syed Ibrahim, G. P.; M. Isloor, Arun; Al Ahmed, Amir; Lakshmi, B. (Journal of Applied Membrane Science & Technology, 2017)
Mixed matrix membranes (MMMs) of Polysulfone (PSf)-Zeolite ZSM-5 (ZZSM-5) were prepared by phase inversion method with a dose ranging from 1.0 to 4.0 Wt. % with polyvinylpyrrolidone (PVP) as the fore forming agent. The prepared mixed matrix membranes were scrutinized for their permeation, hydrophilicity and anti-fouling nature. Characterization of the membrane was carried out by Electrokinetic analyzer. The heavy metal ions rejection experiment has been carried out and the results manifested that, the PZM-4 membrane exhibits higher pure water flux of 348.88 L/m2 h, contact angle of 72.7o and the heavy meals rejection of Pb2+ (98.54%) and of Cd2+ (95.32%) ions. Taken as a whole, the modified PSf-ZZSM-5 ultrafiltration membranes are the attractive candidate for the water treatment.